Activity of Zymomonas mobilis on ethanol products made of cashew nut apple (Anacardium occidentale) with different sources of nitrogen - AKHMAD MUSTOFA; SURANTO SURANTO (Smujo International, 2009)
Abstract. Mustofa A, Suranto. 2009. Activity of Zymomonas mobilis on ethanol production made of cashew nut apple (Anacardium occidentale) with different sources of nitrogen. Nusantara Bioscience 1: 105-109. This research is aimed at identifying Zymomonas mobilis in producing ethanol through batch fermentation process (in 24, 48 and 72 hours) using cashew nut apple extract (red, green and yellow variety) and urea, ammonium sulfate, extract of green peanut sprout and extract koro (Mucuna pruriens) as sources of nitrogen. The research showed that green cashew nut extract with ammonium sulfate in 24 hours of fermentation produced ethanol in optimum result. This treatment had pH of 5.87, 7.64 g/100 mL of sugar (with 48.44% of consumption), 8.0x107 amount of bacterium (µ = 0.154) and production of ethanol equal to 33.02 g/L (Ye = 90.19%).